INTER-STATE VARIATIONS IN ENROLMENT IN HIGHER EDUCATION IN INDIA - C. VIJAYALAKSHMI AND R. ANNAPOORANI (ZENITH International Journal of Multidisciplinary Research, 2013)
Higher education is a critical pillar of human development forming the capstone of traditional education system. It provides not only the high-level skills necessary for labour markets, but also the training essential for teachers, doctors, engineers, civil servants, scientists, entrepreneurs and other professionals. There are 19 states and union territories in which GER is lower than the national average (10.84 percent). In this context the research study on “Inter-State variations in enrolment in higher education in India” was formulated with the objectives of finding out the gender disparities in higher education, the interstate variations in higher education and identify the factors determining gross enrolment of women in higher education. The study was related to 16 major states of India for 2009-2010 and 2010-11 the required data were compiled from selected educational statistics. 2010, Women statistics in India 2010 and Census 2011. The study estimated gender disparity index, Theil’s inequality index and Discriminant analysis. As per the study in the reference period the average gross enrolment rate of women in higher education was lower (41.45) than that of men (58.55). The gender disparity index in enrolment in higher education was found to be the highest in Bihar and lowest in Kerala. The estimated Theil’s inequality index in higher education, number of colleges was found to be higher (0.2344). The estimated discriminate function was statistically valid as indicated by Mahalanobis ‘D’ squared value is 5.727. Enrolment rate in higher education was found to be the highest in Andhra Pradesh and lowest in Bihar. To measure the higher education the cost of higher education is to be minimized and scholarships can be given to motivate into higher education, In higher education job oriented courses can be introduced as a part of the curriculum to make women suitable for employment and establishing an accreditation that ensures quality higher education.